Neurocognitive pathways in Attention-Deficit Hyperactivity Disorder and white matter microstructure - Bessette, Katie L. (Biol Psychiatry Cogn Neurosci Neuroimaging, 2018)
BACKGROUND: This study sought to identify Attention-Deficit Hyperactivity Disorder (ADHD) abnormalities in relationships between brain white matter structure and individual differences in several types of impulsive behavior. METHODS: Sixty-seven ADHD, Combined subtype, and 68 non-ADHD adolescents were given neuropsychological tests and diffusion tensor imaging (DTI) scans. Principal component analysis (PCA) reduced test scores into factors representing different types of impulsive behavior. Tract-based spatial statistics (TBSS) quantified white matter integrity in relationship to components of impulsive behavior. ADHD versus non-ADHD differences in the strength and nature of linear relationships between regional white matter and three impulsivity components were examined using multiple regression. RESULTS: PCA found three separate impulsivity-related factors that were interpreted as motor response inhibition, impulsive choice, and delay aversion. Relationships between regional fractional anisotropy and response inhibition or impulsive choice did not differ between ADHD and non-ADHD. There was a significant interaction between diagnostic group and delay aversion test performance relationships with regional fractional anisotropy. For non-ADHD youth, greater anisotropy in numerous tracts predicted better delay aversion test performance. In contrast, anisotropy in regions including the corpus callosum, corona radiata, internal capsule, and corticospinal tracts either had a negative or no relationship with delay aversion test performance in ADHD. CONCLUSIONS: The results provide additional support that different proposed etiological pathways to ADHD have discretely different neurobiological features. Large disorganization of white matter microstructure appears to contribute to reward-based ADHD pathways rather than motor inhibition.